PENERAPAN METODE IMLA’ MANQUL PADA SISWA SMPQ DARUL FATTAH BANDAR LAMPUNG - Anwar, Khairil (STIT Darul Fattah Bandar Lampung, 2021)
This research is based on a lack of knowledge about Arabic writing skills, students do not have a basic knowledge and still lack of practice in writing Arabic. In this study, researchers used the Imla 'Manqul method, which is moving writing from certain media to textbooks and dictating it. The purpose of this research is